2022
DOI: 10.3389/fbioe.2022.914280
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Feasible Strategies for Arbutin Production

Abstract: Arbutin is a hydroquinone glucoside and a natural product present in various plants. Arbutin potently inhibits melanin formation. This property has been exploited in whitening cosmetics and pharmaceuticals. Arbutin production relies mainly on chemical synthesis. The multi-step and complicated process can compromise product purity. With the increasing awareness of sustainable development, the current research direction prioritizes environment-friendly, biobased arbutin production. In this review, current strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Tyrosinase is a key enzyme that controls melanogenesis [ 10 ]. The suppression of melanin biosynthesis can be achieved by inhibiting tyrosinase activity or reducing the protein expression of melanogenic enzymes, including tyrosinase [ 5 , 6 , 7 , 8 , 9 , 10 ]. Therefore, we examined the direct inhibitory effect of Hir on tyrosinase activity using a cell-free mushroom tyrosinase system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosinase is a key enzyme that controls melanogenesis [ 10 ]. The suppression of melanin biosynthesis can be achieved by inhibiting tyrosinase activity or reducing the protein expression of melanogenic enzymes, including tyrosinase [ 5 , 6 , 7 , 8 , 9 , 10 ]. Therefore, we examined the direct inhibitory effect of Hir on tyrosinase activity using a cell-free mushroom tyrosinase system.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions can lead to a deterioration in quality of life and are clinical and cosmetic concerns worldwide. Therefore, the development of melanin production inhibitors is important for controlling hyperpigmentation, and considerable efforts have led to the discovery of many melanin inhibitors, such as hydroquinone [ 5 ], kojic acid [ 6 , 7 ], and arbutin [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has suggested that the hydroquinone skeleton could have been formed by the removal of the propyl side chain of certain phenylpropane derivatives, e.g., cinnamic acid and phenylalanine. However, there are several reports available in the literature that describe various engineered and artificial methods for enhanced biosynthesis of arbutin [164]. For example, Shen et al [165] demonstrated an artificial pathway in Escherichia coli for increased production of arbutin from simple carbon sources.…”
Section: Distribution Of Arbutin (1) In the Plant Kingdommentioning
confidence: 99%
“…In addition to its skin whitening property which has been known for at least seven decades, arbutin (1) has been shown to possess various other therapeutically relevant biological properties, e.g., antioxidant, antimicrobial and anti-inflammatory [164,165]; it also has the potential as an anticancer agent [166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181]. Information obtained from the published literature on arbutin shows that this compound possesses cytotoxic properties against several human cancer and tumor cell lines including bladder, bone, brain, breast, cervical, colon, gastric, liver, prostate and skin cancers (Table 2) [166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181].…”
Section: Anticancer Potential Of Arbutinmentioning
confidence: 99%
“…15 Besides, it also has the characteristics of promoting fast scarless wound healing. 16 Due to the higher tyrosinase inhibitory activity of α-arbutin (10 times compared to β-arbutin), in addition to the low synthetic yield of β-arbutin, 11,17 it becomes imperative to explore the possibility of enhancing α-arbutin production. Therefore, α-arbutin is a promising biomolecule in industrial production.…”
Section: ■ Introductionmentioning
confidence: 99%